Critical digital ischemia secondary to ulnar artery thrombosis in suspected antiphospholipid syndrome - CC, Tan; NM, Nik Azlan (Pusat Perubatan Universiti Kebangsaan Malaysia, 2023)
Antiphospholipid syndrome (APS) is known to cause critical limb ischemia leading to limb loss or death from arterial occlusion. We reported a 45-year-old woman with critical digital ischemia and was suspected secondary to APS. This woman presented to the Emergency Department (ED) for the third time because of recurrent pain and numbness in the fingertips of her left hand with bluish discoloration of the left little finger. Her ulnar artery became faint on palpation, and her left fifth finger was cool, cyanotic, with prolonged capillary refill time (CRT) and unrecognised signal in SpO2. Angiography and ultrasound showed proximal thrombosis of the ulnar artery. Thrombectomy was performed twice because graft thrombosis had occurred during the first operation. The rheumatology team treated her as APS and administered antiplatelet drugs. We hope this case report will raise awareness among emergency physicians for early recognition and provide optimal treatment.